The Construction of Female Identity in Jun’ichiro Tanizaki’s Naomi: Male Gaze and Unreliable Narration - Luthfiana Dwi Rakhmawati; M. Irfan Zamzani (Ruang Kata, 2026)
In Jun’ichiro Tanizaki’s Naomi, the complex image of female identity is constructed in the interaction between Joji Kawai and Naomi, a young lady to whom male desire, Westernised modernity, and patriarchal power all contribute. The challenge that this study takes up is that Naomi is commonly read as a modern woman or moga, but her identity is mediated through Joji’s first-person narration. This study attempts to explore how the female identity of Naomi is produced via the male gaze and unreliable storytelling. This study combines a qualitative literary method with a close reading approach. The data were extracted from selected narrative sections, character descriptions, and dialogues in the novel that indicate Joji's perception, control, and interpretation of Naomi. The data were studied via the lenses of male gaze theory, unreliable narration, narratology, and the concept of identity creation. The results imply that Naomi is not produced as a stable and self-defined female subject but as a figure constructed through Joji’s desire, fantasy, envy, and patriarchal gaze. His gaze places Naomi as an object of beauty, education, possession, and worry, over and over, and his self-justifying narration makes his story unreliable. The study finds that the picture of Naomi as attractive, manipulative, childlike, or dangerous should be regarded as a creation made through a biased male narrative perspective and not as an objective truth.